The Effect of Governance on Zakat Funds of Indonesian Islamic Commercial Banks with Company Size as a Moderating Variable - Finashih, Nizzah (Universitas Islam Negeri Raden Intan Lampung, 2024)
Zakat collection and distribution in Islamic banking is poor compared to the zakat potential that should exist in Indonesia, even though zakat is regarded as a social performance of Islamic banking and thus demands more attention from companies. This study aims to look at how corporate governance affects Islamic Commercial Banks’ zakat funds in Indonesia. This study's population comprises seven ICBs registered with the OJK between 2011 and 2020. Purposive sampling is used in this study. The research method used was quantitative, with panel data regression analysis performed using Eviews. Corporate governance relies on the size of the board of directors and the Sharia Supervisory Board (SSB). The study's findings reveal that the size of the board of directors and the SSB have little effect on zakat funds. Company size cannot act as a moderating variable for the size of the board of directors or the size of the SSB with zakat funds. Control variables such as profitability and bank size substantially impact zakat funds. The most significant factor influencing zakat funds is bank size.